A Study of Clinical Environment Stressors in Male and Female Students of Dezful University of Medical Sciences Iran - Mojtaba Raji; Leila Masoudiyekta; Armin Tajfar; Mostafa Ajaman; Nosrat Bahrami (Kerman University of Medical Sciences, 2017)
Background & Objective: Clinical teaching in nursing education is of such importance that it is recognized as the heart of professional nursing education Therefore this study aimed to determine clinical environment stressors in male and female students of Dezful University of Medical Sciences Iran in 2015 Methods: This descriptionanalytical study was conducted on 234 nursing and operation room students who were in their second semester or higher and had passes a minimum of 1 unit of clinical training The subjects were entered into the study through a census The data collection tool consisted of a twopart questionnaire including demographic characteristics and the researchermade Clinical Stressful Factors Questionnaire Data analysis was performed using descriptive (mean and standard deviation) and inferential (Spearmans correlation) statistics in SPSS software Results: The main stressor in students of both sexes was related to unpleasant feelings and the least prevalent stressor was related to the field of interpersonal communication The questions that obtained the highest and lowest scores respectively were inadequate and incomplete treatment of patients due to poverty and oral medications administration as an area of clinical practice Conclusion: In order to reduce stress and to create conditions necessary for medical students to learn clinical skills counseling and educational workshops on adaptive coping strategies are recommended for students and lecturers It is hoped that through these measures the damaging physical and mental effects of stress can be prevented in medical students and their learning can be increased